Enhanced Cloud Security using Hybrid Mechanism of RSA, AES and Blowfish Data Encryption with Secure OTP - Singh, Gurjeet; Garg, Dr. Mohita (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2018)
Cloud Computing has become one of the most talked about technologies in recent times and has got lots of attention from media as well as analysts because it is offering lots of opportunities. Enterprises have been determined to reduce computing costs and for that reason most of them started using it in IT technology then adapted virtualization technology. Cloud computing has revolutionized the way computing and software services are delivered to the clients on demand. It offers users the ability to connect to computing resources and access IT managed services with a previously unknown level of ease. Thus, security concerns among users of the cloud have become a major barrier to the widespread growth of cloud computing. In this research work, we have used the 3 step security mechanism for the keeping the data secure at the cloud. We have implemented the strong authentication mechanism using md5 encrypted OTP and enhanced the security of data using Cloud Broker and RSA, Blowfish and AES. When you log on to your machine and then try to access a resource, say a file server or database, something needs to assure that your username and password are valid. With sensitive data stored in the cloud of the different users, we need a strong authentication mechanism along with OTP. Data breaches because of no/weak authentication. Afterwards we have verified the integrity of data stored at cloud provider using SHA2. Multiple parameters like processing time, processing cost, AES,RSA and blowfish encryption time, OTP generation and encryption time have been calculated and analyzed. We have been able to enhance the security by optimizing the processing time as well as processing cost. After implementing the proposed methodology, it has been summarized that the cloud security can be enhanced by applying the proposed mechanism. The proposed system has reduced the complexity, processing cost which increases the overall efficiency of the system.